ORGANISASI HIMAPEM UNIVERSITAS DARMA AGUNG BINA DESA PUNCAK LOLOMATUA MENJADI DESA WISATA: HIMAPEM UDA PHP2D community service in Puncak Lolomatua Village, Ulunoyo District, South Nias Regency - Sitearo Ndruru; Moirongo Laia; Besti Rohana Simbolon (Politeknik Negeri Sriwijaya, 2021)
Puncak Lolomatua, Ulunoyo District, South Nias Regency, is the highest mountain peak in Nias. The location is suitable for enjoying the view of seeing Nias Island as a whole. However, the road to the location is not smooth because it is still made of clay which is partially filled with sharp stones. The majority of the people are farmers and are classified as low-income. The Village Development and Empowerment Holistic Program Team (PHP2D) Himapem Fisipol UDA which focuses on poverty alleviation and tourism schemes provides empowerment and guidance to village community institutions to encourage villages to become tourist sites in 2022. The method used is the preparation of program plans, collecting materials and data. buy it, and make a schedule. Then the implementation stage is by conducting socialization, counseling, coaching, revamping Puncak Lolomatua by changing the physical form of Puncak Lolomatua which is difficult to reach into easy to reach and making photo spots and tidying up plants and fostering the community to manage Puncak Lolomatua Village into a tourist destination. The results of the service are: 1 ). There is a change in the way of thinking, 2) raising awareness of the potential of the village, 3) developing community skills to add new photo spots at Puncak Lolomatua , 4). The community is passionate about preserving cleanliness and introducing the latest developments of Puncak Lolomatua 4). The community began to develop Puncak Lolomatua into a tourist location 5). The village cooperates with Darma Agung University. Keywords: Abdimas, PHP2D, Himapem, Puncak Lolomatua, Tourism Village